The Concept of Benefidonors in Sustaining Community Development through Individual Member Waqf Beneficiaries - Ali, Ahmad Fahme Mohd; Zal, W. A. Amir; Johari, Fuadah; Abd Hamid, Baharom; Nik Zirwatul (Universitas Muhammadiyah Malang, 2026)
This study investigates the role of waqf in sustaining community development through a novel hybrid concept termed “benefidonors” individuals who simultaneously function as both beneficiaries and donors within the waqf ecosystem. Drawing on prosumerism, ConsuMerchant behavior and the Islamic principle of mutual cooperation (ta’awun), it is posits that active participation through sharing, using and re-donating waqf, significantly enhance multiple dimensions of community well-being. Using a quantitative approach, data were collected via a structured survey instrument administered to 304 verified waqf beneficiaries from the Yayasan Waqf Malaysia database, representing diverse socio-demographic backgrounds across Peninsular Malaysia. The instrument, validated through pilot testing (n = 50) and expert review, employed multi-item Likert scales adapted from established literature to measure seven outcome variables: human capital, physical health, religious capital, family development, social capital, quality of life, and economic capital. Structural Equation Modeling (PLS-SEM) was used for data analysis. Results indicate that the benefidonor concept exerts a significant influence across all seven domains, with particularly strong effects on economic and human capital. While the study offers actionable insights for waqf institutions such as developing digital platforms to facilitate sharing, usage, and re-donation it is limited by its cross-sectional design and focus on existing beneficiaries, which may constrain generalizability. Nonetheless, the findings underscore the potential of transforming passive recipients into active co-creators of sustainable community development through the benefidonor model.